Full-length 16S rRNA gene long-read sequencing from dried cervicovaginal fluid - Borgmästars, Emmy; Enroth, Stefan; Lindberg, Julia Hedlund; Sundfeldt, Karin; Gyllensten, Ulf (Uppsala University, 2025)
This dataset refers to the 16S rRNA gene long-read sequencing data described in the article "Full-length multiplexed 16S rRNA gene sequencing works well in self-collected decade old cervicovaginal fluid on paper cards" (unpublished). DNA was extracted from two 3 mm punches of paper cards containing dried cervicovaginal fluids that had been stored for up to eleven years at room temperature. Full-length 16S rRNA gene amplicons (~1.5 kb) were generated using the Kinnex 16S protocol followed by long-read sequencing using the Pacific Biosciences (PacBio) Revio system. The raw fastq files consist of de-multiplexed and circular consensus sequencing reads. A more detailed description of the methods can be found in the paper.
Keywords: Other health sciences not elsewhere classified; Translational and applied bioinformatics; Genomics and transcriptomics; Microbial genetics; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik; Other Health Sciences; Annan hälsovetenskap